2022
DOI: 10.3390/nu14142863
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nutrition Literacy Assessment Instrument for Chinese Pregnant Women

Abstract: The study was designed to develop and validate the nutrition literacy assessment instrument for pregnant women in China (NLAI-P). The dimension, components and questions of NLAI-P were identified via literature review and expert consultation. A panel of experts evaluated the content validity. The construct validity was evaluated by using the exploratory factor analyses (EFA) and confirmatory factor analyses (CFA). Cronbach’s α coefficient and split-half reliability were applied for examining the reliability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Earlier studies identified NL measurement scales with different domains (15,(24)(25)(26)(27), or a series of specific items without considering its domains (28)(29)(30). In China, a serial of core items of NL were established for general people (31), pregnant women (32), preschool children (33), and old people (34). Based on dietary risks and dietary guidelines for Chinese people, our previous study (35) developed the NL measurement scale with 43 items (NL-43) for Chinese adults with strong reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies identified NL measurement scales with different domains (15,(24)(25)(26)(27), or a series of specific items without considering its domains (28)(29)(30). In China, a serial of core items of NL were established for general people (31), pregnant women (32), preschool children (33), and old people (34). Based on dietary risks and dietary guidelines for Chinese people, our previous study (35) developed the NL measurement scale with 43 items (NL-43) for Chinese adults with strong reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
“…The Nutrition Literacy Assessment Instrument for Pregnant Women in China (NLAI-P) is employed to measure participants’ nutritional literacy [ 53 ]. Participants respond to 38 questions across three dimensions: knowledge literacy, behavior literacy, and skill literacy.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the emotional usefulness and symbolic expressiveness of cultural and environmental preservation options are incorporated [48][49][50]. Evidence indicates that the high emotional value perceived in organic products increases the estimated probability of healthy purchasing the following year, increasing conscious eating behaviors [50,51]. Therefore, this hypothesis is proposed:…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%